Liana communities exhibit different species composition, diversity and community structure across forest types in the Congo Basin. (19th April 2020) - Mumbanza, Francis M.; Bauters, Marijn; Kearsley, Elizabeth; Boeckx, Pascal; Lubini, Constantin A.; Verbeeck, Hans
Abstract: Lianas are poorly characterized for central African forests. We quantify variation in liana composition, diversity and community structure in different forest types in the Yangambi Man and Biosphere Reserve, Democratic Republic of Congo. These attributes of liana assemblages were examined in 12 1‐ha plots, randomly demarcated within regrowth forest, old growth monodominant forest, old growth mixed forest and old growth edge forest. Using a combination of multivariate and univariate community analyses, we visualize the patterns of these liana assemblage attributes and/or test for their significant differences across forest types. The combined 12 1‐ha area contains 2, 638 lianas (≥2 cm diameter) representing 105 species, 49 genera and 22 families. Liana species composition differed significantly across forest types. Taxonomic diversity was higher in old growth mixed forests compared to old growth monodominant and regrowth forests. Trait diversity was higher than expected in the regrowth forest as opposed to the rest of forest types. Similarly, the regrowth forest differed from the rest of forest types in the pattern of liana species ecological traits and diameter frequency distribution. The regrowth forest was also less densely populated in lianas and had lower liana total basal area than the rest of forest types. We speculate that the mechanism of liana competitive exclusion by dominant tree species is mainly responsible for the lower liana species diversity in monodominant compared to mixed forests. We attribute variation in liana community structure between regrowth and old growth forests mostly to short development time of size hierarchies.